(untitled) (Research, Society and Development, 2022)
Background: Species of mycotoxin-producing fungi are potentially dangerous to humans and animals. The liver is the best-known organ of action of these substances. The aim of this study was to isolate microscopic fungi from honey and investigate the cytotoxic effect of the extract of Penicillium sp. in an experimental model. Methods: Honey samples were cultured in Sabouraud agar. After isolated and identified microscopically, the colonies of the genus Penicillium sp. were transplanted to the Sabouraud dextrose agar culture medium. After its development, they were processed to obtain an extract. Eighteen Wistar mice were randomly assigned to experimental (GI) and control (GII) groups. The GI was subjected to an oral inoculation of the extract, while GII received a placebo. Procedures were performed every day for thirty days, after which the liver of each animal was removed for analysis. Results: Aspergillus sp. (86.2%), Geotrichum sp. (6.89%) and Penicillium sp. (6.89%) were isolated. The most frequent species was Aspergillus niger (46%). In relation to the cytotoxic effects of the extract of Penicillium sp., the gross findings in the liver of GI suggested mainly congestion. Light microscopy showed that the little hepatic lobules were preserved and there was vascular congestion of sinusoids. Light microscopy of specimens from the experimental group showed that 68.2% were abnormal, whereas 87.5% of the control group were within normal limits. Conclusions: The results suggest that there was contamination in honey samples. There was a predominance of macroscopic and microscopic changes in the liver of experimental rats, suggesting liver damage by Penicillium sp.